1993
DOI: 10.1177/026921559300700109
|View full text |Cite
|
Sign up to set email alerts
|

Methodological difificulties in rehabilitation research

Abstract: This paper presents an overview of some of the pitfalls and suggests ways of improving the quality of research into rehabilitation after stroke. The aims of rehabilitation are outlined and methodological problems inherent in this area discussed, including spontaneous recovery, multidimensional outcomes, definition of treatment and placebo effects. Major weaknesses found in the rehabilitation literature are identified and recommendations for improvement made, including the need for comparable controls, adequate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Despite the methodological difficulties attached to rehabilitation research [7,8], many meta-reviews carried out subsequently have concluded that rehabilitation brings about significant gains in terms of personal autonomy and the ability to return home, return to work and participate in family and civic life [9][10][11]. Yet, in a healthcare climate of seemingly infinite demand and limited Correspondence: Dr Andrew D. Worthington, West Heath House, 54 Ivy House Road, West Heath, Birmingham B38 8JW, UK.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the methodological difficulties attached to rehabilitation research [7,8], many meta-reviews carried out subsequently have concluded that rehabilitation brings about significant gains in terms of personal autonomy and the ability to return home, return to work and participate in family and civic life [9][10][11]. Yet, in a healthcare climate of seemingly infinite demand and limited Correspondence: Dr Andrew D. Worthington, West Heath House, 54 Ivy House Road, West Heath, Birmingham B38 8JW, UK.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that stroke units reduce disability through an integrated programme of rehabilitation that allows therapeutic strategies to continue beyond formal therapy (Stroke Unit Trialists' Collaboration 1997a). However, the effect of informal therapy, such as that provided by nurses, is unclear since it is hard to quantify (Pollock et al 1993). While there is general recognition that the nursing contribution to the outcomes of stroke rehabilitation is important this has received little specific research attention.…”
Section: Introductionmentioning
confidence: 99%
“…1997). However, despite accumulating evidence of numerous stroke rehabilitation strategies, there is no general consensus regarding the specific role of the nurse in rehabilitation and their impact on its continuity still is debated (Pollock et al. 1993, Forster & Young 1996, Burton 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In many developed countries, stroke care has been radically changed following a Cochrane review (Stroke Unit Trialists' Collaboration 1997a,b) demonstrating that 'organised in-patient care' (stroke units) significantly improved mortality and morbidity poststroke (Indredavik et al 1997). However, despite accumulating evidence of numerous stroke rehabilitation strategies, there is no general consensus regarding the specific role of the nurse in rehabilitation and their impact on its continuity still is debated (Pollock et al 1993, Forster & Young 1996, Burton 2003.…”
Section: Introductionmentioning
confidence: 99%